The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.3329/icpj.v1i4.10061
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant property and polyphenols evaluation of aqueous root extract of Decalepis hamiltonii Wight & Arn.

Abstract: Antioxidant activity, total phenol and flavonoids estimation of the aqueous extract of the tuberous root of Decalepis hamiltonii was evaluated by free radical scavenging activity using 2,2-diphenylpicryl-1-picrylhydrazyl (DPPH), metal chelating activity, superoxide scavenging activity, ferric reducing antioxidant power assay (FRAP) and 2,2'azinobis (3-ethylbenzothiozoline-6-sulfonic acid) disodium salt (ABTS•+) assay. The content of polyphenols in the extract was determined by spectrophotometrically, calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Transition metals in our biological system combine with antioxidants to form chelate. Then it inhibits the formation of OHthat finally suppresses the lipid peroxidation in biomolecules (Samydurai and Thangapandian, 2012). In our Ferrous (Fe ++ ) ion chelating ability test we observed that, crude methanol extract exhibited best Fe ++ chelating capability (IC50 = 25 μg/mL) comparing to standard, EDTA (IC50 = 25 μg/mL) and n-Hexane fraction showed the less Fe ++ chelating ability (IC50 = 46 μg/mL).…”
Section: Discussionmentioning
confidence: 81%
“…Transition metals in our biological system combine with antioxidants to form chelate. Then it inhibits the formation of OHthat finally suppresses the lipid peroxidation in biomolecules (Samydurai and Thangapandian, 2012). In our Ferrous (Fe ++ ) ion chelating ability test we observed that, crude methanol extract exhibited best Fe ++ chelating capability (IC50 = 25 μg/mL) comparing to standard, EDTA (IC50 = 25 μg/mL) and n-Hexane fraction showed the less Fe ++ chelating ability (IC50 = 46 μg/mL).…”
Section: Discussionmentioning
confidence: 81%
“…In one of the study shows that poly-phenols content in the aqueous root extracts of Decalepis hamiltonii is high and these extracts exhibit strong antioxidant activities compared to that of the standard compounds such as α-Tocoperol, Rutin and Butylated hydroxytoluene (BHT) [36]. Hence, this investigation suggested that the plant naturally having rich source of antioxidants could be used in the prevention of free radical diseases and general health tonic.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, a lower value of IC 50 indicates the highest antioxidant activity of 51.92±11.19 and 70.10±8.28 µg/ml, respectively (Table 1). Similarly, reported Samydurai and Thangapandian [13] the Decalepis hamiltonii (Asclepiadaceae) aqueous root extract showed good antioxidant activity could be used in the prevention of free radical diseases and general health tonic. The generation of free radicals can bring about thousands of reactions and thus cause extensive tissue damage.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 87%